Experimental study on thermal performance improvement of building envelopes by integrating with phase change material in an intermittently heated room. (April 2018) - Li, Yanru; Zhou, Jing; Long, Enshen; Meng, Xi
Highlights: This study focus on the actual heating operation in the south of China. An experiment was taken to study the heat storage and release process of building envelope integrated with PCM during intermittent heating process. The heat release process of the PCM layer lasted 6-7h after the suspension of heating. The inner surface heat flux of the PCM wall was 18.48% lower than the reference wall in the heating process of the four conditions. Abstract: The intermittent heating is frequently used to save the building heating energy consumption. Both the heat storage and release processes of building envelope have coupling influences on the indoor thermal environment during intermittent heating process. In order to make the best of the heat storage and release process to adjust the indoor thermal environment, this paper integrated phase change material (PCM) with the building envelope and experimentally studied the thermal performance improvement under four typical intermittent heating conditions summarized by questionnaires in China. The results show that the inner surface temperature of the PCM wall increased faster after heating, which was more favorable to ensure that the indoor thermal environment recovers to the thermal comfort state quickly. The inner surface temperature of the PCM wall was higher than the reference wall after heating was off, which can maintain a constant indoor air temperature. In the heating process of the four conditions, the inner surface heat flux value was 18.48% lower than the reference wall. Integrating PCM with the building envelope can not only improve the indoor thermal environment, but also reduce the heating time and heating energy consumption.